OLD SCHOOL LINGUISTICS MADE NEW— REVIEW OF Contemporary Linguistics: An Introduction. 5th ed. By William O’Grady, John Archibald, Mark Arnoff, and Janie Rees-Miller. New York: Bedford/St. Martin’s, 2005. Pp. xxvi + 684. - Chris Wen-chao Li (Taiwan Journal of Linguistics)
Amidst the recent explosion of interest in linguistic science and the subsequent publication of large numbers of introductory works on the subject, O'Grady et al.'s Contemporary Linguistics (5th ed.) stands out as a solid general purpose primer directed at an academic audience. Written by some eighteen contributors specializing in each of the seventeen branches of linguistics covered, topics are judiciously chosen while drawing on current scholarship and integrating different theoretical persuasions, without losing sight of the book's target readership. The result is an up-to-date text balanced in its treatment of subject matter and perspectives--a work that lives up to its moniker of "Contemporary" Linguistics.